Management Of Fully Edentulous Patient with Semi-Adjustable Articulator: A Case Report - Reinaldo, Evander; Rikmasari, Rasmi; Damayanti, Lisda (Indonesian Journal of Prosthodontic, 2021)
Introduction: Loss of tooth could cause many anatomical, physiological, and functional changes, also could cause psychological trauma. Patient who loss all their tooth needed denture to fulfil their needs, both functionally and esthetically. Case report: This article showed treatment for 71 years old man came to Universitas Padjadjaran Dental Hospital with chief complaint pain in left mandibular ridge from the past 6 months and couldn’t masticate well. This patient wore acrylic full denture made by denturist from the past 7 years. Intraorally, both occlusion at posterior part of the denture were open, found enlargement of palatal mucosa because usage of vacuum chamber dan mandibular flat residual ridge. Treatment plan of this patient was fabrication upper and lower denture with facebow transfer and semi adjustable articulator. Discussion: Full denture in flat ridge cases needed proper treatment because lack of retention and stability. Extension of denture flange at sublingual area could increase stability and retention in this case. Fabrication of full denture with facebow could record maxillary relation with rotation of the mandible and allowed maxillary cast model placed according to the semi adjustable articulator. Semi adjustable articulator was an effective tool to fabricate full denture because could minimize adjustment of artificial tooth and occlusal contact. Conclusion: The usage of facebow and semi adjustable articulator could help dentist to achieved artificial teeth arrangement like patient occlusal scheme while function so that dentist could minimize reduction and adjustment of artificial teeth also increased patient’s comfort while wearing the denture.